Dynamics of connected cruise control systems considering velocity changes with memory feedback. (March 2015) - Yu, Shaowei; Shi, Zhongke
Abstract: In this paper, a new connected cruise control strategy considering multiple preceding cars' velocity changes with memory is designed to improve roadway traffic mobility, enhance traffic safety and reduce fuel consumptions and exhaust emissions. The linkage between multiple preceding cars' velocity changes with memory and the following car's acceleration or deceleration is explored by using the empirical car-following data and the gray correlation analysis method, and then an improved car-following model considering multiple preceding cars' velocity changes with memory in the connected cruise control strategy is put forward to investigate the effects of multiple preceding cars' velocity changes with memory on each car's speed and acceleration, the relative distance, fuel consumptions, CO, HC and NOX emissions. The new connected cruise control strategy is designed to be able to receive signals of velocity changes with memory from multiple cars ahead through wireless vehicle-to-vehicle communication and the immediately ahead car's relative distance and velocity difference by radar. The results of numerical simulations prove that multiple preceding cars' velocity changes with memory have significant effects on car-following behaviors and that using multiple preceding cars' velocity changes with memory feedback in designing a connected cruise control system can improve roadway traffic mobility, enhance traffic safety and reduce fuel consumptions and exhaust emissions.